a) - 7 elevado 2 =
b ) ( - 7 ) 2 =
c ) 2 elevado 4 =
d ) ( - 2 ) 4 =
e ) ( - 3 ) 4 ) =
f ) - 3 elevado 4 =
Soluções para a tarefa
Respondido por
1
Olá boa noite!
![a) \: { - 7}^{2} = ( -7) \times ( - 7) = 49 a) \: { - 7}^{2} = ( -7) \times ( - 7) = 49](https://tex.z-dn.net/?f=a%29+%5C%3A+++%7B+-+7%7D%5E%7B2%7D++%3D+%28+-7%29+%5Ctimes+%28+-+7%29+%3D+49)
![b) { (- 7})^{2} = 49 b) { (- 7})^{2} = 49](https://tex.z-dn.net/?f=b%29+%7B+%28-+7%7D%29%5E%7B2%7D++%3D+49)
![c) \: {2}^{4} = 2 \times 2 \times 2 \times 2 = 16 c) \: {2}^{4} = 2 \times 2 \times 2 \times 2 = 16](https://tex.z-dn.net/?f=c%29+%5C%3A++%7B2%7D%5E%7B4%7D++%3D+2+%5Ctimes+2+%5Ctimes+2+%5Ctimes+2+%3D+16)
![d) \: ( - 2) ^{4} = 16 d) \: ( - 2) ^{4} = 16](https://tex.z-dn.net/?f=d%29+%5C%3A+%28+-+2%29+%5E%7B4%7D++%3D+16)
![e) \: ( - 3)^{4} = 3 \times 3 \times 3 \times 3 = 81 e) \: ( - 3)^{4} = 3 \times 3 \times 3 \times 3 = 81](https://tex.z-dn.net/?f=e%29+%5C%3A+%28+-+3%29%5E%7B4%7D++%3D+3+%5Ctimes+3+%5Ctimes+3+%5Ctimes+3+%3D+81)
![f) { - 3}^{4} = 81 f) { - 3}^{4} = 81](https://tex.z-dn.net/?f=f%29++%7B+-+3%7D%5E%7B4%7D++%3D+81)
Perguntas interessantes